Muslim-Christian relations in central Asia - Van Gorder, A. Christian (Central Asian studies series, 2008)
Explores issues of cultural tension that affect Muslim and Christian interaction within the Central Asian context. This book looks at the ways that Christians have interacted with Central Asian Muslims in the past, and discusses what might need to be done to improve Muslim-Christian relations in the region